Botulotoxin as the most typical product of the biotechnology for aesthetic cosmetology and the study of subjective attitude towards its use among the Ukrainian population sample - Filiptsova, Olga; Naboka, Olga; Khokhlenkova, Natalia; Kalashnik, Kateryna; Kaliuzhnaia, Olha; Dvinskykh, Nataliia; Soloviova, Alina; Zakhariev, Andriy; Petrovska, Liudmyla (ScienceRise: Biological Science, 2024)
The aim of the study was to analyze the effectiveness of botulinum therapy in aesthetic cosmetology and to consider the influence of various factors on the decision to perform the procedure. Materials and methods. The work used content analysis of literary sources, analytical method, and online survey of females and males of different generations regarding the botulinum therapy procedure. Results and discussion. Botulinum toxin was historically first used to smooth glabellar wrinkles, and then its use was expanded to other areas of the face. There are seven types of botulinum toxin (A, B, C, D, E, F, and G). Experience with the use of botulinum therapy for aesthetic purposes shows that clinical ineffectiveness is extremely rare. Depending on gender, the reaction to procedures with the introduction of botulinum toxin for cosmetic purposes is different. Females are more aware of the botulinum therapy procedure than males. Botulinum toxin therapy is most common among younger adults (25 to 39 years old). Conclusions. Interest in botulinum toxin therapy increases with age. People, interested in botulinum toxin therapy, are more likely to visit a cosmetologist regularly. Profession affects person’s involvement in the botulinum toxin therapy procedure. The largest proportion of the respondents who have undergone botulinum toxin therapy is observed among the medical and beauty sectors, business and management. The largest number of the respondents who want to try botulinum toxin therapy is among students. This may indicate the openness of the younger generation to experiments and understanding the importance of continuing their youth in the future for as long as possible. The study showed that BMI does not affect respondents’ involvement in the botulinum toxin therapy procedure. The Internet is the main source of information about botulinum toxin therapy for a significant number of the respondents, regardless of their involvement in this procedure. The participants prioritize the result of botulinum toxin therapy, not its cost